The Role of Safety Leadership in Safety Behavior with Safety Climate as a Mediation Variable: A Study on Construction Workers of Alfath Group South Kalimantan (Real Estate Developer) - Ariyadi, Eko; Meiske Claudia (HM Publisher, 2022)
The quality of leadership (safety leadership) and organizational climate (safety climate) have a significant impact on organizational performance (safety behavior). Working in an organization with a good climate will stimulate job potential. Safety climate and safety leadership are important issues in construction companies, one of which is the real estate construction company Alfath Group, which has been operating since 2016 in South Kalimantan. The location of the Alfath group project is in Banjarmasin, Banjarbaru and Tanah Laut Regency, South Kalimantan. This study aims to evaluate the role of safety leadership on safety behavior with safety climate as a mediating variable in order to prevent work accidents in order to increase worker productivity. This study is an observational study with an explanatory research approach which was conducted on 100 respondents of Alfath group workers. Data analysis was carried out using the SMART-PLS program. Safety leadership has a significant effect on safety behavior, safety leadership has a significant effect on safety climate, safety climate has a significant effect on safety behavior, and safety climate mediates the influence of safety leadership on safety behavior.